Śrī Santa Gajānana gītāmrta - Durgesh, 1919- (Santa caritra gītamālā, 1971)
Poems on the life of Gajanan Maharaj of Shegaon, Maharashtra, d. 1910, with an introduction to each poem; previously serialized in Janabhāvanā, Marathi weekly.